Screening Of Free Radical Scavenging Activity and Immuno-Modulatory Effect Of Jwaramurarirasa - Dhumale, Omkar K; Rudrapuri, Mahantesh B; Mohan, G Vinay (International Research Journal of Ayurveda & Yoga, 2021)
Jwaramurari Rasa is one of the herbo mineral formulation having property of Rasayana (rejuvenation therapy). Recent study shown the presence of phytochemical like alkaloids, carbohydrates, steroids, flavonoids, proteins, saponins, and tripenoids. Hence antioxidant and immunomodulatory activity are expected with Jwaramurari Rasa. In this regard to provide evidence to establish the facts mentioned in classics an attempt was made to assess the free radical scavenging activity of Jwaramurari Rasa. Jwaramurari Rasa was subjected for screening of free radical scavenging activity by Superoxide dismutase (SOD), Catalase, Glutathione, Malondialdehyde (MDA) test. Immunomodulatory activity by phagocytosis, candidacidal assay, neutrophil locomotion chemotaxis, and Nitrobluete trazolium (NBT) test. 5%, 12.5%, 25%, 50% and 100% concentration of the samples were used. Jwaramurari Rasa has shown significant immunomodulatory activity. 100% (95%) solution of Jwaramurari Rasa has shown highly significant result with NBT test stimulation of neutrophils than control. In candidacidal activity of Jwaramurari Rasa with100% was highly significant. Jwaramurari Rasa has shown significant results with Candidacidal, Phagocytosis and Chemotaxis than control.